G113(P) The effects of sleeping position and maternal smoking on the ventilatory response to hypoxia. (7th April 2014) - Rossor, T; Ali, K; Trenear, R; Hannam, S; Rafferty, GF; Greenough, A
Abstract : Aims: Both prone sleeping and maternal antenatal smoking are known risk factors for Sudden Infant Death Syndrome (SIDS). The aim of this study was to determine whether the two factors could act together to impair the ventilatory response to hypoxia. Methods: Healthy infants without congenital abnormalities, born at 36 weeks post menstrual age or greater were recruited from the postnatal ward. Mothers were asked about their smoking habits and urine samples were obtained for cotinine analysis and infants assigned to the "smoking" or control group accordingly. A nasal mask was attached to a pneumotachograph and side-stream sampling capnograph; the outputs were recorded using Spectra. Respiratory gas was delivered at 4 litres/minute through a non-return valve. In both the prone and supine position baseline ventilation was first measured for five minutes whilst the infant was breathing medical air. Subsequently, the infant's ventilatory response to inhalation of 15% oxygen balanced with nitrogen was measured for five minutes. The challenge was stopped if the oxygen saturation dropped below 85%. Minute volume was calculated on a 10 second average. Baseline, maximum and minimum minute volume (MV) were calculated. The time to the maximum MV was calculated. Infants respond to hypoxia with a biphasic response, first an increase then a decline in ventilation. The rate of decline was calculated as the rate at which MV declined following the maximum MV. Results: 14 control infants and 7 infants of mothers who had smoked in pregnancy (median 10, range 2–20 cigarettes/day) were studied. Following exposure to 15% oxygen in the prone position, the hypoxic rate of decline was greater in the smoking group: median 3.8 (range 1.6–16.7)ml/kg/min/s compared to the control group: median 0.7 (range 0.1–5.4) ml/kg/min/s, p = 0.011. There was no significant difference between the two groups in the rate of decline in the supine position. Conclusion: Our results suggest that an impaired ventilatory response to hypoxia may explain the vunerability to SIDS of infants of smoking mothers when sleeping in the prone position.